Royal heirs in imperial Germany : the future of monarchy in nineteenth-century Bavaria, Saxony and Württemberg /: the future of monarchy in nineteenth-century Bavaria, Saxony and Württemberg. ([2017]) - Müller, Frank Lorenz, 1970-
No abstract available